2020
DOI: 10.1371/journal.pone.0233894
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-expandable versus self-expanding transcatheter aortic valve replacement for bioprosthetic dysfunction: A systematic review and meta-analysis

Abstract: Background Transcatheter aortic valve-in-valve (VIV) procedure is a safe alternative to conventional reoperation for bioprosthetic dysfunction. Balloon-expandable valve (BEV) and self-expanding valve (SEV) are the 2 major types of devices used. Evidence regarding the comparison of the 2 valves remains scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
“… References 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 …”
Section: Supporting Informationunclassified
“…The perception that the future belongs to SE TAVR is self-perpetuating, which is astonishing with respect to clinical realities. Huge cohort studies repeatedly showed key advantages of BE (33-37) the most prominent being the persistently higher need for a permanent pacemaker (PPM) with SE devices (33)(34)(35)(38)(39)(40)(41)(42), even if used for valvein-valve procedures (43). The acceptance of these drawbacks by many clinicians in HICs is partly because the implantation of a pacemaker is affordable.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 45 consecutive patients with failed Mitraflow valves and valve-in-valve (ViV) TAVI with CoreValve (Medtronic) and Evolut R valves showed favorable early outcomes with TAVI for degenerated Mitraflow bioprosthesis. This procedure provided an important gateway to avoiding high-risk redo surgery and is now a potential option for degenerated surgically implanted aortic Mitraflow valves ( 1 ) A study, involving 3,940 patients comparing balloon-expandable valves and self-expandable valves in ViV procedures, showed larger post-procedural effective orifice area with self-expandable valves, but also higher post-procedural pacemaker implantation necessity ( 2 ). Our patient already had a pacemaker implanted so we decided to use an Evolut R valve.…”
Section: Discussionmentioning
confidence: 99%